Annexin A5 promotes macrophage activation and contributes to pulmonary fibrosis induced by silica particles. (September 2016) - Luo, C; Ji, X; Fan, J; Hou, Z; Wang, T; Wu, B; Ni, C
Objective: To investigate the contributions and underlying molecular mechanisms of annexin A5 toward silica-induced pulmonary fibrosis. Methods: Male C57BL/6 mice were randomly divided into three groups and instilled intratracheally with silica, saline, or air. Mice were euthanized at 3, 7, 14, or 28 days following treatment. Annexin A5 levels in serum and lung tissues were detected by enzyme-linked immunosorbant assay (ELISA) assays or Western blots. The association of annexin A5 levels with silica-induced lung fibrosis was further investigated in the macrophage cell line, RAW264.7. Following exposure of these cells to silica at a concentration of 200 μg/ml for 6 or 12 h, the expression levels of transforming growth factor β1 (TGF-β1), interleukin 1α (IL-1α), Fas ligand (FasL), and their downstream targets were evaluated by Western blots. Furthermore, annexin A5 and FasL were knocked down by small interfering ribonucleic acid (siRNA) and TGF-β1 secretion into the cell culture medium was measured by ELISA assays or Western blots. Results: Mice treated with silica demonstrated lung fibrosis at 28 days following exposure, whereas, in controls, only mild and transient inflammation was evident at day 3 and day 7 postinstillation and was not present at day 14. Furthermore, silica-exposed mice exhibited significantly ( p < 0.05) elevated levels of annexin A5 in serum and lung tissues, relative to control groups. Consistent with these findings, silica exposure of RAW264.7 cells for 6 or 12 h, led to an annexin A5-dependent increase in the expression levels of TGF-β1, IL-1α, FasL, and their downstream target molecules. These silica-induced changes were reversed by siRNA-mediated knockdown of annexin A5, but downregulation of FasL led to increased annexin A5 expression and reduced levels of TGF-β1, IL-1α, and FasL downstream target molecules. Conclusions: These findings define a role of annexin A5 in promoting macrophage activation via Fas/FasL pathways in silica-induced lung fibrosis.